2003
DOI: 10.1097/01.jcp.0000085408.08426.05
|View full text |Cite
|
Sign up to set email alerts
|

Mirtazapine Orally Disintegrating Tablet Versus Sertraline: A Prospective Onset of Action Study

Abstract: This multinational, randomized, double-blind study was specifically designed to prospectively compare the onset of antidepressant efficacy of mirtazapine orally disintegrating tablets and sertraline at dosages commonly used in clinical practice. A total of 345 patients with major depressive episode (DSM-IV) received mirtazapine (30-45 mg/d) or sertraline (50-150 mg/d) for 8 weeks. Mirtazapine was administered in the newly developed fast dissolving, orally disintegrating tablet formulation. Assessments were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(52 citation statements)
references
References 20 publications
1
49
0
2
Order By: Relevance
“…In our study, we have observed significant changes in mood, suicidal ideation items, anxiety and insomnia clusters during the first week of treatment with mirtazapine ODT. Rapid reduction of suicidal thoughts and anxiety is in line with data of other naturalistic studies and previous clinical studies, showing that mirtazapine has a faster onset of action compared to paroxetine, sertraline, or venlafaxine extended-release tablets (16)(17)(18)(19). Referring to the Lithuanian situation with a very high number of suicides, it is important to have rapid acting antidepressants like mirtazapine ODT (20).…”
Section: Discussionsupporting
confidence: 73%
“…In our study, we have observed significant changes in mood, suicidal ideation items, anxiety and insomnia clusters during the first week of treatment with mirtazapine ODT. Rapid reduction of suicidal thoughts and anxiety is in line with data of other naturalistic studies and previous clinical studies, showing that mirtazapine has a faster onset of action compared to paroxetine, sertraline, or venlafaxine extended-release tablets (16)(17)(18)(19). Referring to the Lithuanian situation with a very high number of suicides, it is important to have rapid acting antidepressants like mirtazapine ODT (20).…”
Section: Discussionsupporting
confidence: 73%
“…Removal of ODT from the tongue is also more diffi cult than for the standard (coated) olanzapine tablet (SOT) since it forms an amorphous residue that can only be removed by scraping the tongue. The use of orally disintegrating tablets in other indications (eg, migraine, depression), has been successfully tested in other studies (Dowson et al 2002;Behnke et al 2003). Improved compliance has, besides improved cognitive functioning and reduced negative symptoms, also been identifi ed as a possible factor leading to a decrease in suicidality (Meltzer et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In a global questionnaire study of patients' perceptions of mirtazapine ODT (n = 5428), 86% reported finding it easy to use and had a positive impression of this formulation. These opinions translated into a greater preference for mirtazapine ODT compared with ordinary tablets (62.1% preferred the ODT) and increased rates of compliance (47.3% of patients reported that their compliance had improved) [57].…”
Section: Odts In Psychiatric Carementioning
confidence: 99%